General and comparative efficacy and effectiveness of antidepressants in the acute treatment of depressive disorders: a report by the WPA section of pharmacopsychiatry. - Baghai, T; Blier, P; Baldwin, D; Bauer, M; Goodwin, G; Fountoulakis, K; Kasper, S; Leonard, B; Malt, U; Stein, D; Versiani, M; Möller, H (2011)
Current gold standard approaches to the treatment of depression include pharmacotherapeutic and psychotherapeutic interventions with social support. Due to current controversies concerning the efficacy of antidepressants in randomized controlled trials, the generalizability of study findings to wider clinical practice and the increasing importance of socioeconomic considerations, it seems timely to address the uncertainty of concerned patients and relatives, and their treating psychiatrists and general practitioners. We therefore discuss both the efficacy and clinical effectiveness of antidepressants in the treatment of depressive disorders. We explain and clarify useful measures for assessing clinically meaningful antidepressant treatment effects and the types of studies that are useful for addressing uncertainties. This includes considerations of methodological issues in randomized controlled studies, meta-analyses, and effectiveness studies. Furthermore, we summarize the differential efficacy and effectiveness of antidepressants with distinct pharmacodynamic properties, and differences between studies using antidepressants and/or psychotherapy. We also address the differential effectiveness of antidepressant drugs with differing modes of action and in varying subtypes of depressive disorder. After highlighting the clinical usefulness of treatment algorithms and the divergent biological, psychological, and clinical efforts to predict the effectiveness of antidepressant treatments, we conclude that the spectrum of different antidepressant treatments has broadened over the last few decades. The efficacy and clinical effectiveness of antidepressants is statistically significant, clinically relevant, and proven repeatedly. Further optimization of treatment can be helped by clearly structured treatment algorithms and the implementation of psychotherapeutic interventions. Modern individualized antidepressant treatment is in most cases a well-tolerated and efficacious approach to minimize the negative impact of otherwise potentially devastating and life-threatening outcomes in depressive disorders.